2004
DOI: 10.1002/jcb.20249
|View full text |Cite
|
Sign up to set email alerts
|

A fragment of the hypophosphatemic factor, MEPE, requires inducible cyclooxygenase‐2 to exert potent anabolic effects on normal human marrow osteoblast precursors

Abstract: MEPE, 56.6 kDa protein isolated from tumors associated with hypophosphatemic osteomalacia, increases renal phosphate excretion and is expressed in normal human bone cells. AC-100, a central 23-amino acid fragment of MEPE, contains motifs that are important in regulating cellular activities in the bone microenvironment. Thus, we assessed in vitro effects of AC-100 on multipotential normal human marrow stromal (hMS) cells that have the capacity to differentiate into mature osteoblasts. Proliferation was quantifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…MEPE was first identified in tumor conditioned medium and osteosarcoma cell lines. Multiple experimental observations support that MEPE is correlated positively to serum P i and has an important role in negative regulation of mineralization in the skeleton (26,27).…”
Section: Clustering Analysis Indicates Pth-(1-34)-treated Samples Havmentioning
confidence: 92%
“…MEPE was first identified in tumor conditioned medium and osteosarcoma cell lines. Multiple experimental observations support that MEPE is correlated positively to serum P i and has an important role in negative regulation of mineralization in the skeleton (26,27).…”
Section: Clustering Analysis Indicates Pth-(1-34)-treated Samples Havmentioning
confidence: 92%
“…In contrast, MEPE has been shown to have an anabolic effect on osteoblast differentiation. It is reported that AC-100 enhances osteogenesis by promoting osteoblast proliferation and differentiation like BMP-2 (8,9). Dentonin, which is the same as AC-100, promotes dental pulp stem cell proliferation in response to the dentin repair response (34,35).…”
Section: Mepe Expression Is Strongly Stimulated By Bmp-2 Treatment Anmentioning
confidence: 99%
“…Two functional domains of MEPE have been well defined; one is the centrally located motif that includes an RGD, cell adhesion domain, and a SGDG, glycosaminoglycan (GAG) interaction domain. AC-100, a 23-amino acid synthetic peptide comprised of RGD and SGDG, has demonstrated strong osteogenic activity (8,9). The other domain is a C-terminal ASARM motif that is common among the SIB-LING family proteins although they are not functionally conserved (10).…”
mentioning
confidence: 99%
“…Mature osteoblast function is less influenced by the addition of truncated MEPE or AC-100. Evidence suggests that MEPE may be mediating some of its effects through the production of prostaglandins 29 and since COX-2 protein levels have been shown to correlate with integrin activation, 30 MEPE activation of FAK could likely shift the balance of cell:ECM interactions that result in COX-2 regulation. Furthermore, evidence suggests that PGE2 primarily acts in the first few days of in vitro models of osteogenesis to increase the numbers of cells likely to become mature osteoblasts.…”
Section: Discussionmentioning
confidence: 98%
“…Evidence suggests that AC-100 functions through the activation of integrins and that subsequent regulation of prostaglandin signaling through control of COX-2 is responsible for its ability to regulate osteoblast differentiation. 11 These observations have led to the possibility that AC-100 may have potential for use in the treatment of bone diseases associated with decreased bone formation and as part of surgical therapies.…”
mentioning
confidence: 98%